Comparison of 10 cm and 50 cm Long Iodine Cells in Iodine-Stabilized Diode Laser-Pumped Nd:YAG Laser at 532 nm - Prayut Potirak; Monludee Ranusawud; Pichet Limsuwan; Prathan Buranasiri (My University, 2018)
An iodine-stabilized diode laser-pumped Nd:YAG laser system at 532 nm was developed at the National Institute of Metrology of Thailand (NIMT) for the first time in Thailand. Two iodine cells with the lengths of 10 and 50 cm were used for the comparison of frequency stability of Nd:YAG laser. The experiment was set for phase modulation spectroscopy. The Nd:YAG laser was locked to the a10 component of the R(56)32-0 transition of iodine molecule. The variation of wavelength with time and the frequency stability were carried out at various iodine cell temperatures of 20, 10, 5, 1, -1, -3 and -5°C. The results from the frequency stability measurements showed that the lowest Allan standard deviation value of 6.643×10-10 was obtained at -5°C for 50 cm long iodine cell. From this Allan standard deviation value, it can be concluded that the iodine-stabilized diode laser-pumped Nd:YAG laser system at 532 nm developed in this study is acceptable to be used with a gauge block interferometer for the length calibration of the gauge block.
Keywords: Allan variance; Advanced Measurement and Metrology Techniques